Standard Fatwa in Legislation; Compliance with Required Interests - Mohsen Jahangiri; Muhammad Ali Bannaei Kheyrabadi (آموزه‌‌های فقه مدني)
Shia fiqh in the situation to respond individual needs and in meaningful distance from social notion has been developed and grown. The book of Ijtihad (Arabic: اجتهاد meaning: use of reason to arrive at a knowledge of truth in religious matters) and taqlid (Arabic: تقلید meaning: “following” or “imitation” of a legal expert by a nonexpert) also is not an exception to this rule. Since in some subjects which are analyzed from the point of the personal matters in confronting with social problems, it has come to theoretical deadlock and some of these problems are not resolved through personal fiqh method. One of these important cases is to establish statutes in accordance with Islam decrees. Law enactment not only has had a vital importance in old political philosophy but also is counted the heart of modern democracies in contemporary periods. There are problems and issues in this field. One of these issues is “Standard Fatwa in legislation” i.e. if there is a conflict between fatwas (Arabic: فتوی meaning: authoritative legal opinions given by Islamic jurists) with which of them the Islamization of statutes is judged the fatwa of governing, most learned jurists. the jurists of the Guardian Council, efficient fatwa, compliance with precaution, well-known fatwa. After presenting these theories and important problems which these theories include the present paper shows discordance between two aspects “personal aspect and social aspect” for referring ahkam, from one side and from the other side it has stated the theory of fatwa Compliance with required interests and has provided some theoretical required backgrounds. The diminution (lowering) of the requirements of the special fatwa in Law enactment to the cases of realizing mandatory interests and explain how the allowance in act according to fatwa in some regulations related to the personal affairs is of the conceptual bases of this theory.